Applying an Optimization Algorithm Based on the Cauchy Distribution for Active and Reactive Power Management with Batteries in Energy Distribution Systems - Vega Peña, Maria Camila; Montoya Giraldo, Oscar Danilo; Gil-González, Walter (Ingeniería, 2025)
Context: This study developed an energy dispatch model (EDM) using the Cauchy-based distribution optimizer (CbDO) for coordinating battery energy storage units (BESUs) and photovoltaic (PV) sources in medium-voltage distribution networks, aiming to minimize energy losses and operating costs while observing to network constraints. Method: The CbDO was implemented in MATLAB and benchmarked against the continuous genetic algorithm (CGA), the parallel particle swarm optimizer, the parallel vortex search algorithm, and a semidefinite programming (SDP) approach. The analyzed scenarios included unitary and variable power factor operation in order to test optimization performance. Results: The CbDO outperformed traditional methods, achieving lower energy losses and CO2 emissions, closely matching the SDP method's results in variable power factor scenarios. The most significant gains were observed when all DERs operated flexibly, validating our proposal's effectiveness in complex non-convex problems. Conclusions: The CbDO is a viable and efficient solution for EDM, providing near-SDP performance with a simpler implementation. BESU integration and flexible power factor operation can notably enhance grid efficiency.